Exploring citizenship competencies in Pancasila subjects through local wisdom in the Merdeka curriculum - Suryaningsih, Anis; Winarno, Winarno; Hed, Norhafiza Mohd; Widiatmaka, Pipit (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
Teachers are at the forefront of building students' competencies for junior high school education, especially local wisdom-based civic competence, but during the implementation of the independent curriculum, the competencies mastered by students are still not optimal. This study aims to ascertain the level of local wisdom-based civic competence that students possess, the challenges that Pancasila subjects present to students in developing local wisdom-based civic competence, and potential solutions for fostering local wisdom-based civic competence in the era of independent curricula. This research was conducted at SMP Negeri 1 Pacitan, and the research subjects were students. This research uses a qualitative approach and a descriptive research method because it tries to describe the competencies mastered by students, the obstacles to building them, and solutions to these obstacles, especially those related to local wisdom-based civic competence in the era of an independent curriculum. Data collection techniques are interviews, observation, and documentation, and the data analysis used is interactive data analysis. Students have not been able to master civic competence optimally because they have not been able to implement civic disposition optimally and master civic disposition and civic skills more. This can happen because there are several obstacles, namely less than optimal teacher competence, unsupportive facilities and infrastructure, teachers being often late in starting lessons, poor student ethics towards teachers, and still teachers who cannot utilize digital-based learning media. The solution that needs to be done is for the government to make a policy to provide education and training to teachers related to understanding and implementing the Merdeka curriculum. This needs to be done so that each teacher can improve his competence so that his role in the learning process can increase civic competence based on local wisdom in students.